(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
Institutions of higher education have to face fierce competition, which brings the importance of ambition and firmness, marketing approach and also the indispensability of strategies to be established. In the ever-changing education system – where the frosh ratios, the hierarchy of universities bear a major part – it is needed to influence the decision of the would-be students to choose our university and our services. It is important to position it well that all the participants involved – the students of now and the future, the lecturers and all the staff in the university – commonly share the open opportunities and the tasks assigned. The institution has to develop a unique image which excels and characterized it well. By the help of it, one could be different from other such institutions and it is necessary to stitch closer relationship of citizens in other campuses in order to commonly share the university itself. The Dancing University Project is an excellent opportunity of Pécs and also the University of Pécs.